The effects of selected trading strategies on the value of closed-end investment trusts: A test of the efficiency of the Johannesburg Stock Exchange - Narendra Bhana (South African Journal of Business Management, 1993)
Closed-end investment funds listed on the Johannesburg Stock Exchange invariably trade at discounts from their net asset value. The purpose of this article is to test a series of trading rules to determine whether an investor can capitalize on these discounts to earn excess returns. The buy-and-sell points strategy produced returns significantly in excess of these obtainable by holding the market portfolio or by following a buy-and-hold strategy. Using standard deviation of return as a proxy for risk, the results fail to confirm that an investor had to accept significantly more risk to earn a larger return. However, there is no assurance that the same strategies will produce excess returns in the future. The trading strategies tested over the 1979-88 period may require adjustments in today's market.
Keywords: 650